3
$\begingroup$

I see the following sequence and it's: $$h=1+4+4^2+\cdots+4^{X+Y}=\frac{4^{X+Y+1}-1}{4-1}$$

how we get this sequence?

I know this is a primary question but I confused :)

$\endgroup$
  • $\begingroup$ Do you mean, how does one prove the formula for the sum of terms? $\endgroup$ – Travis Willse Aug 24 '14 at 16:55
  • $\begingroup$ Dear @Travis, I means how get this? $\endgroup$ – Mouna Mokhiab Aug 24 '14 at 16:56
3
$\begingroup$

This is an example of a geometric series. Let's say we try to sum: $$S=1+r+r^2+r^3+\dotsb+r^n$$ In your example, $r=4$, and $n=X+Y$.

There is a well known "trick" for solving this. Multiply by $r$: $$Sr=r+r^2+r^3+\dotsb+r^n+r^{n+1}$$ Notice how this is the same thing as $S$, except without the $1$ at front and with an extra $r^{n+1}$ at the end. In fact: $$Sr=S-1+r^{n+1}$$ Solving: \begin{align} Sr&=S-1+r^{n+1} \\ Sr-S&=-1+r^{n+1} \\ S(r-1)&=r^{n+1}-1 \\ S&=\frac{r^{n+1}-1}{r-1} \end{align}

$$\fbox{$1+r+r^2+r^3+\dotsb+r^n=\dfrac{r^{n+1}-1}{r-1}$}$$

Plugging in $r=4$ and $n=X+Y$, we get your answer.

$\endgroup$
  • $\begingroup$ can we say sum is: $((4^{X+Y+1}-1)/3)-1?$ $\endgroup$ – Mouna Mokhiab Aug 24 '14 at 17:28
  • $\begingroup$ No. Why do you have the $-1$ at the end? It should just be: $$\frac{4^{X+Y+1}-1}{4-1}=\frac{4^{X+Y+1}-1}{3}$$without any $-1$s at the end. (If you were summing $4+4^2+\cdots+4^{X+Y}$ rather than $1+4+4^2+\cdots+4^{X+Y}$, then sure.) $\endgroup$ – Akiva Weinberger Aug 24 '14 at 17:33
  • $\begingroup$ you means $4+...+4^X+Y=((4^{X+Y+1}-1)/3)-1 $ am I right? $\endgroup$ – Mouna Mokhiab Aug 24 '14 at 17:35
  • $\begingroup$ Yes. If we were to start with $4+\dotsb$ rather than $1+4+\dotsb$, then you would have to subtract off the $1$. However, in your Original Post, you asked the question with the $1$. $\endgroup$ – Akiva Weinberger Aug 24 '14 at 17:37
  • $\begingroup$ yes, thankssss so muchhhhh $\endgroup$ – Mouna Mokhiab Aug 24 '14 at 17:38
0
$\begingroup$

$$x^n-1=(x-1)(x^{n-1}+x^{n-2}+\cdots+x+1)$$

$\endgroup$
0
$\begingroup$

This is a GP, where $a= $ first term=$1$, $r=$common ratio=$4$

Sum of GP is given by $\frac{a(r^n-1)}{r-1}$

$1+\underbrace{4+4^2+\cdots+4^{X+Y}}$
$1+\hspace{25 pt}X+Y\hspace{30 pt}$=n=Number of terms

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.